The Role of Mediation in Purchase Intention in Affecting the Decision to Purchase Health Supplement Products - Fidia, Fidia; Christiarini, Renny (https://jurnal.binamandiri.ac.id/, 2024)
Customer interest in health products has surged due to the COVID-19 virus, impacting the world, including Indonesia. This encourages the community to consistently maintain the cleanliness of their surroundings and fulfill nutritional needs to strengthen the immune system by consuming healthy food and beverages. However, the nutritional content in food and beverages still needs to be improved, requiring the support of health supplements to help meet these nutritional requirements. This research examines the effect of quality, price, e-WOM, celebrity endorser, and brand image on purchase decisions, with purchase intention as the intervening factor. The data collected from 334 respondents who consume health supplements in Batam were analyzed using the Structural Equation Model (SEM). This research states that price does not significantly affect purchase decisions; however, quality, e-WOM, celebrity endorser, and brand image positively and significantly affect purchase decisions. Additionally, the research results indicate that price does not significantly affect purchase decisions when mediated by purchase intention. Meanwhile, the mediating role of purchase intention on quality, e-WOM, celebrity endorser, and brand image significantly affects purchase decisions.